REDUCING INCIDENT OF ARI THROUGH HEALTH EDUCATION WITH EXERCISE METHOD CLEAN AND HEALTHY LIFESTYLE FOR FIFTH GRADE STUDENTS AT ELEMENTARY SCHOOL OF SEMAMPIR 1 KEDIRI - Sandy Kurniajati (Suluh Adiluhung Publisher (SAPub), 2024)
Acute Respiratory Infection (ARI) is an infectious disease of upper and lower respiratory tract caused by infectious agents. ARI can be transmitted directly or indirectly. ARI attacks more common in children. The problem, many students infected with ARI and transmission of ARI is also high. This health education starting from requesting permission letters, making proposals. The community service aims to increase students' understanding of ARI and how to prevent it, which increasing the behavior of maintaining a clean and heathy life and reducing the prevalence rate of acute respiratory tract infections in students at Elementary School of Semampir I Kediri. The population is 28 of fifth grade students. The results of the pre-test given before the education was carried out showed that the number of students who scored in category of 39% poor, 54% moderate, and 7% good. Students can answer questions related to knowledge about preventing acute respiratory infections. In post-test result, students received scores in the categories of 14% poor, 47% moderate, and 39% good. Results were that health education regarding clean and healthy lifestyle with methods Power-Point and effective exercise to increase students' knowledge and awareness regarding preventing the transmission of ARI.